(359) مبادىء النظرية الاحصائية وتطبيقاتها) الجزء الأول) (Principles of Statistical Theory and its Applications(2Parts - محرم وهبى محمود (معهد التخطيط القومي, 2026)
يتناول هذا المحتوى مجموعة من المفاهيم الأساسية في علم الإحصاء، حيث يبدأ بالاحصاء الوصفي الذي يشمل جداول التوزيع التكرارية والتمثيل البياني، مثل المدرج التكراري والمضلع التكراري. كما يتناول مقاييس النزعة المركزية، بما في ذلك المتوسطات كالأوسط الحسابي والوسيط والمنوال. يُعالج أيضًا مقاييس التشتت، مثل المدى والانحراف المعياري، بالإضافة إلى خصائص التباين ومعامل الاختلاف. يتناول البحث أيضًا معامل الالتواء والتفرطح، وخصائص العزوم لتوزيع تكراري معلوم. يُستعرض مفهوم الارتباط من خلال معامل ارتباط بيرسون وسبيرمان، وخطوط الانحدار مع التركيز على كيفية إيجادها. كما يُناقش مفهوم الاحتمالات وبعض النظريات المرتبطة بها، بالإضافة إلى العزوم والدالة المولدة للعزوم. يتضمن المحتوى أيضًا دراسة التوقعات، بما في ذلك القيمة التوقعية والخطأ المعياري. أخيرًا، يتناول بعض التوزيعات المتصلة وغير المتصلة، مثل توزيع جاما وتوزيع ثنائي الحدين، بالإضافة إلى منحنيات بيرسون. يُظهر هذا البحث أهمية الإحصاء في تحليل البيانات واتخاذ القرارات المستندة إلى الأدلة. This content covers a range of fundamental concepts in statistics, beginning with descriptive statistics, which includes frequency distribution tables and graphical representation, such as histograms and frequency polygons. It also addresses measures of central tendency, including averages like the arithmetic mean, median, and mode. Additionally, it discusses measures of dispersion, such as range and standard deviation, along with the properties of variance and the coefficient of variation. The research further explores skewness and kurtosis, as well as the moments of a known frequency distribution. The concept of correlation is examined through Pearson's and Spearman's correlation coefficients, and regression lines are highlighted with a focus on how to derive them. The discussion extends to probabilities and associated theories, as well as moments and moment-generating functions. Expectations are also analyzed, including expected values and standard errors. Finally, the content addresses some continuous and discrete distributions, such as the gamma distribution and the binomial distribution, along with Pearson curves. This research demonstrates the importance of statistics in data analysis and evidence-based decision-making.